Assessing cotton defoliation, regrowth control and root rot infection using remote sensing technology - Yang, Chenghai; Greenberg, Shoil M.; Greenberg, Shoil M.; Everitt, James H.; Everitt, James H.; Fernandez, Carlos J.; Fernandez, Carlos J. (International Journal of Agricultural and Biological Engineering, 2011)
Cotton defoliation and post-harvest destruction are important cultural practices for cotton production.? Cotton root rot is a serious and destructive disease that affects cotton yield and lint quality.? This paper presents an overview and summary of the methodologies and results on the use of remote sensing technology for evaluating cotton defoliation and regrowth control methods and for assessing cotton root rot infection based on published studies.? Ground reflectance spectra and airborne multispectral and hyperspectral imagery were used in these studies.? Ground reflectance spectra effectively separated different levels of defoliation and airborne multispectral imagery permitted both visual and quantitative differentiations among defoliation treatments.? Both ground reflectance and airborne imagery were able to differentiate cotton regrowth among different herbicide treatments for cotton stalk destruction.? Airborne multispectral and hyperspectral imagery accurately identified root rot-infected areas within cotton fields. ?Results from these studies indicate that remote sensing can be a useful tool for evaluating the effectiveness of cotton defoliation and regrowth control strategies and for detecting and mapping root rot damage in cotton fields.? Compared with traditional visual observations and ground measurements, remote sensing techniques have the potential for effective and accurate assessments of various cotton production operations and pest conditions. Keywords: remote sensing, cotton defoliation, regrowth control, root rot, reflectance spectrum, airborne multispectral imagery, airborne hyperspectral imagery DOI: 10.3965/j.issn.1934-6344.2011.04.001-011 ? Citation: Yang C, Greenberg S M, Everitt J H, Fernandez C J. ?Assessing cotton defoliation, regrowth control and root rot infection using remote sensing technology. ?Int J Agric & Biol Eng, 2011; 4(4): 1